TOLERANCE OF STUDENTS OF PERTUKARAN MAHASISWA MERDEKA (PMM) 4 AT BOSOWA UNIVERSITY - Muh. Fitrah Ramadhan Umar; Andi Muhammad Aditya S; Nurhikmah Nurhikmah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to describe the tolerance of Pertukaran Mahasiswa Merdeka (PMM) students in Makassar City. This research method uses descriptive qualitative research method. There were 10 respondents in this study with a sampling method, namely purposive sampling with the criteria that the respondents were inbound students of Pertukaran Mahasiswa Merdeka (PMM) 4 at Bosowa University. Data collection methods through observation and open interview. Data processing is done by collecting data, reducing data, presenting data and drawing conclusions. The results of this study are that all respondents practiced mutual tolerance with different religions and cultures characterized by mutual respect and esteem, not demeaning different tribes, considering students of different cultures and religions as brothers, not discriminating, and not discriminating between cultures and religions.